2019
DOI: 10.1080/0284186x.2019.1646432
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose and pathological response in oesophageal cancer patients treated with neoadjuvant chemoradiotherapy followed by surgery: a multi-institutional analysis

Abstract: Purpose: To explore whether a higher neoadjuvant radiation dose increases the probability of a pathological complete response (pCR) or pathological major response (pMR) response in oesophageal cancer patients. Material and methods: Between 2000 and 2017, 1048 patients from four institutions were stratified according to prescribed neoadjuvant radiation doses of 36.0 Gy (13.3%), 40.0 Gy (7.4%), 41.4 Gy (20.1%), 45.0 Gy (25.5%) or 50.4 Gy (33.7%) in 1.8-2.0 Gy fractions. Endpoints were pCR (tumour regression grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…17,18 Similarly, the pCR group in our study demonstrated significantly better 5-year OS and DFS than did the non-pCR group. Although there had been several studies on the relevant factors affecting pCR, [19][20][21] few had investigated the predictive value of the percentage decrease of maximal esophageal wall thickness for ESCC treated with NCRT. In this study, the pCR rate was significantly higher in those with a >40% decrease of maximal esophageal wall thickness than in those with ≤40%.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Similarly, the pCR group in our study demonstrated significantly better 5-year OS and DFS than did the non-pCR group. Although there had been several studies on the relevant factors affecting pCR, [19][20][21] few had investigated the predictive value of the percentage decrease of maximal esophageal wall thickness for ESCC treated with NCRT. In this study, the pCR rate was significantly higher in those with a >40% decrease of maximal esophageal wall thickness than in those with ≤40%.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies using National Cancer Data Base reported different results concerning the impact of radiation dose on the survival or pCR rate in esophageal cancer patients receiving neoadjuvant chemoradiation therapy (19)(20)(21)(22); three studies found irradiation dose had no impact on survival of before or after propensity matching, and one study even concluded that 41.4 Gy is associated with superior overall survival, compared to 50.4 Gy (19). Another two retrospective studies also revealed that higher neoadjuvant radiation dose did not enhance pCR rate in esophageal cancer (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, changes in pathological features of the primary disease and lymph nodes in response to NCRT, as well as their prognostic value, have attracted the attention of some researchers. The rate of pathological complete response (pCR; no vital tumor cells in resected specimens or lymph nodes) after NCRT ranges from 27% to 49% (1)(2)(3)(4)(5), indicating that more than half of patients have persistent residual disease after NCRT. Recent evidence suggests that patients with ESCC who reach pCR after NCRT have longer median OS than those with residual tumor (6).…”
Section: Introductionmentioning
confidence: 99%